Efficiency of an Ultrafiltration Process for the Depollution of Pretreated Olive Mill Wastewater - Mohammed Zine; Noureddine Touach; El Mostapha Lotfi; Philippe Moulin (Membranes)
The depollution of constructed wetland-pretreated olive mill wastewater (OMW) using a membrane filtration system was experimentally studied. Dead-end filtration (DEF) was employed to evaluate suitable MF/UF membranes and select the appropriate molecular weight cut-off for optimal OMW treatment. Removal efficiencies for COD (chemical oxygen demand) and TOC (total organic carbon) using DEF reached maximum values of 88.14% and 11.17%, respectively. Adsorption of raw and pretreated OMW on granular activated carbon was also carried out for a comparative study against DEF and pretreatment. The semi-industrial-scale experiments were conducted using commercial ceramic ultrafiltration (UF) membranes (150 and 50 kDa) in cross-flow filtration (CFF) mode at a permeate flux around 200 L h−1 m−2 and a trans-membrane pressure (TMP) of 3.5–3.8 bars. This post-treatment had a significant impact on COD removal efficiency from pretreated OMW, reaching 78.5%. The coupled process proposed in this study achieved removal efficiencies of 97%, 97%, and 99.9% of COD, TOC, and turbidity, respectively.